Site suitability assessment for selected nature-based solution (NBS) in flood-prone area - Ibrahim, Balqis; Ash'aari, Zulfa Hanan; Zulkafli, Zed (Malaysian Institute Of Planners, 2024)
In recent decades, Malaysia has experienced an increase in both the frequency and severity of flood events, making the country particularly susceptible to flooding. Therefore, is a growing recognition of the importance of nature-based solution (NbS) as a viable approach to enhance flood resilience. This study utilized Geographic Information System (GIS) technologies to address this challenge by identifying optimal locations for implementing selected NbS in Kota Tinggi district, Johor. The research involved selecting suitable NbS measures using Multi-Criteria Decision Analysis (MCDA). A two-phased approach was employed. Firstly, RECONECT’s Measure Selector tool, a web-based tool was used to generate a preliminary list of NbS aligned with local conditions in Kota Tinggi. Following the initial screening, MCDA, a decision-making approach that considers multiple criteria was then used to evaluate the shortlisted NbS options. A site suitability analysis was then performed based on slope, distance to rivers, land use and distance to roads. Two NbS options, floodplain restoration and retention ponds, were chosen for further analysis with a more specific requirement. The results identified a total area of 126,798 hectares suitable for NbS implementation based on the general criteria. Floodplain restoration emerged as the more suitable option, with 107,929 hectares (89.67%) meeting the criteria compared to 12,419 hectar (10.33%) for retention ponds. Understanding the potential of NbS for flood mitigation in Kota Tinggi can assist with the selection and implementation of NbS in flood-prone areas to enhance flood resilience and create a more sustainable future.